Whistleblowing in Polish Business Entities in Relation EU Legal Requirements - Skoczylas-Tworek, Agnieszka (Whistleblowing w polskich podmiotach gospodarczych wobec unijnych wymogów prawnych, 2023)
Whistleblowing as a signaling tool for perceived irregularities is now recognized as one of the most important processes that should be implemented in every organization. Its importance and relevance to the proper, lawful operation of an organization is emphasized by the provisions of EU Directive 2019/1937 on the protection of whistleblowers. They focus primarily on the implementation of the rules and procedures to enable whistleblowing and ensure sufficient protection for whistleblowers. The purpose of the paper was to assess the practical aspects of the implementation and dissemination of the whistleblowing tool in selected Polish business entities in the face of the requirements set by EU Directive 2019/1937. The study carried out confirmed the position presented so far in the literature of not providing sufficient and effective tools not only for the implementation of whistleblowing, but also for the protection of whistleblowers. Thus, it showed that most of the surveyed companies are only at the beginning of the path in implementing EU-compliant whistleblowing systems. The reasons for the above should be seen not only on the part of the entities, but also in the delayed process of implementing EU law into national law.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 2, s. 123-133
Keywords: whistleblowing; fraud; abuse; compliance; violation; EU directive; oszustwa; nadużycia; zgodność; nieprawidłowości